Use of Betel Leaves in Pediatric Stoma Care (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: To find out a practicable, cost effective and easily available alternative of commercial stoma care devices for pediatric patients in a developing country.Methods: The study was conducted in the department of Pediatric Surgery in Dhaka Medical College Hospital, Bangladesh, during two years period from May 2009 to April 2011. Number of patients was 162 with age range 2 days to 7 years, mean age 2.3 years. As early as a colostomy or ileostomy had started functioning, a central hole was made in a betel leaf. The hole could just snugly accommodate the stoma. After applying a layer of zinc oxide paste over the peristomal skin the leaf was placed as such the stoma rotrudes through the hole. The smooth shiny surface of the leaf would face upwards and rough surface downwards. Another intact betel leaf with the shiny surface also facing upwards would cover the stoma. The leaves did not act as a reservoir rather simply acted as a barrier between the effluent and the peristomal skin. Fifty seven patients with colostomy and 11 with leostomy used stoma appliances (wafer with bag). Eighty six patients with colostomy and 8 patients with ileostomy used betel leaves and zinc oxide paste. Mean length of time between creation and closure of a colostomy was 9 months and that of an ileostomy was three months. It was ensured that each individual patient had used his or her respective stoma care method till closure of the stomas. Two parameters were used to evaluate the outcome of the above mentioned stoma care methods: (a) peristomal skin excoriation and (b) insultto the stomal mucosa in the form of ulceration.Results: Among the patients who used stoma appliances 21.53% developed peristomal skin excoriation, 7.69% developed mucosal ulceration and 6.34% patients developed local hypersensitivity reaction to stoma adhesive. On the contrary, patients who were managed with betel leaves 20.93% developed peristomal skin excoriation and 8.13% developed mucosal ulceration. No incidence of allergic reaction to local application of betel leaf and zinc oxide occurred. Average cost for betel leaves was less than 0.50 US$ per month in comparison to about 30 US$ for ostomy appliances.Conclusion: Betel leaves may be used as a cheap, easily available, non irritant and effective alternative of commercial appliances to protect the stomas and peristomal skin in pediatric patients.DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19534